Diversity of virulence of Pyricularia oryzae isolates obtained from a single lesion of wheat - da Silveira Lorenset, Mateus; Canabarro, Raissa; Bergmann, Mireli; Antunes da Cruz, Maria Fernanda (Revista Ceres, 2025)
The objective of this study was to evaluate the virulence of Pyricularia oryzae isolates obtained from a single leaf blast lesion on wheat. The wheat cultivars (BRS Louro, BR 18, BRS Tarumã, BRS Parrudo, BRS 208) at the four-leaf stage were inoculated with a suspension of 100.000 conidia/mL. A significant difference was observed in the severity in the cultivars. Among the evaluated isolates, it was possible to observe differences in the susceptibility of the cultivars. Severity data ranged from 3.3 to 99.54% among treatments. Isolates 1 and 2 were the most aggressive for all cultivars tested. The greatest disease severity occurred in the interactions BRS 208 x isolate 1 (99.54%), BRS Louro x isolate 2 (99.34%), and BRS 208 x isolate 2 (99.09%).The lowest disease severity was observed in BRS Tarumã (68%) and BR 18 (75%) cultivars for the isolates 1 and 2, respectively. Isolate 3 presented medium aggressiveness in which the cultivars presented between 44 to 58% of wheat blast severity. The isolate 4 was the least aggressive for all cultivars with severity indexes ranging from 3 to 12%. These data indicate the existence of virulence diversity in P. oryzae isolates obtained from a single lesion.